An Exploration of the Structure of Effective Apologies. (May 2016) - Lewicki, Roy J.; Polin, Beth; Lount, Robert B.
Abstract: Violations of trust are an unfortunate but common occurrence in conflict and negotiation settings: negotiators make promises that they do not keep; parties in conflict behave in unexpected ways, escalating tensions and breaking past trust. What often follows these violations is some form of an account, specifically an apology, in an effort to repair that trust. But are some apologies more effective than others? Two studies reported here examine the structural components of apologies. Six components of an apology were defined from previous research and presented to subjects—singly and in combination—in the form of component definitions and in the context of a trust violation scenario. Results indicate that not all apologies are viewed equally; apologies with more components were more effective than those with fewer components, and certain components were deemed more important than others. Moreover, apologies following competence‐based trust violations were seen as more effective than apologies following integrity‐based violations. Implications and future directions for research in the structure of effective apologies are presented.